Acetone Atmospheric Distribution Retrieved From Space. Issue 5 (7th March 2019) - Franco, B.; Clarisse, L.; Stavrakou, T.; Müller, J.‐F.; Pozzer, A.; Hadji‐Lazaro, J.; Hurtmans, D.; Clerbaux, C.; Coheur, P.‐F.
Abstract: As one of the most abundant oxygenated volatile organic compounds in the atmosphere, acetone (CH3 C[O]CH3 ) influences atmospheric oxidants levels and ozone formation. Here we report the first unambiguous identification of acetone from the nadir‐viewing satellite sounder Infrared Atmospheric Sounding Interferometer (IASI). Via a neural network‐based retrieval approach that was previously applied to the retrieval of other weak absorbers, we obtain daily global acetone retrievals. A first intercomparison with independent measurements is conducted. As the retrieval method is computationally fast, it allowed the full reprocessing of the 2007–2018 IASI time series. Analysis of the retrieved global product and its seasonality suggests that emissions of acetone and precursors from the terrestrial biosphere at Northern Hemisphere middle and high latitudes are the main contributors to the atmospheric acetone abundance, more than year‐round oxidation of anthropogenic isoalkanes. Remarkably, biomass burning does not appear to be a strong global source of acetone. Plain Language Summary: Acetone is an omnipresent atmospheric gas that has a significant impact on atmospheric chemistry, especially on the concentration of other species that can degrade greenhouse gasses like methane. However, its sources remain uncertain and poorly quantified, in part due to the absence of routine measurements. Here we show that acetone can be detected from space by the Infrared Atmospheric Sounding Interferometer (IASI) onboard the Metop satellites. From the IASI measurements, we produce the first daily distributions of acetone abundance at the global scale, using a neural network algorithm. Comparison with acetone measurements made in various aircraft campaigns shows a good agreement. From the analysis of the IASI acetone distribution and variability, we deduce that the dominant source of atmospheric acetone is the terrestrial vegetation at Northern Hemisphere middle and high latitudes. Human activities also contribute to the atmospheric acetone concentrations, although fires do not appear as a strong source globally. Key Points: The atmospheric acetone spectral signature can be unambiguously observed in IASI/Metop satellite infrared spectra First daily global distributions of acetone columns are produced using a neural network‐based retrieval approach Northern Hemisphere biogenic emissions appear as the main acetone source, more than anthropogenic isoalkanes and biomass burning